An updated review: women's concerns following miscarriage on multiple social media platforms - Emily, G. Ong; Lauren, Davis; Rachel, Curiel; Hindi, E. Stohl; Anita, L. Nelson; Nuriya, Robinson (Journal of Women's Reproductive Health, 2023)
This study explored concerns and unsolicited advice relating to miscarriage shared on multiple social media platforms for mentions of questions, advocacy, medical advice, conflicts of interest, and terminology used to describe miscarriage. Public social media posts in English from January 1st, 2019 to June 30th, 2021 were searched using keywords related to miscarriage. A dataset of questions, advice, conflicts of interest, and terminology used was created from eligible posts determined by inclusionary and exclusionary criteria. The dataset was analyzed to identify themes and calculate statistics. Approximately 1000 posts were reviewed and 149 posts were found eligible for analysis. Of the total, 116 posts included advice and a subset of 71 posts offered questions. A total of 152 mentions of advice were identified from the total eligible posts with 82.9% of advice related to advocacy for destigmatizing miscarriage, enhancing community support, or expressing grief. 17.1% of posts offered medical advice eligible for evaluation of which 73% were accurate across all platforms. From the dataset, 103 questions were analyzed for common themes. The four most common themes of questions included grief, self-blame, quality of post-miscarriage counseling in different care settings, and inadequate medical counseling.  This study indicates that women who experience miscarriage have many unanswered questions and powerful feelings relating to grief and self-blame that could have long-term impacts. Social media has become a place for women to self-advocate and connect with others for support, from which clinicians could increase their understanding of women’s unmet needs.
Keywords: Miscarriage; Early pregnancy loss; Spontaneous abortion; Social media; Patient education; Advocacy; Counselling.